2011
DOI: 10.1111/j.1528-1167.2010.02966.x
|View full text |Cite
|
Sign up to set email alerts
|

The adverse event profile of pregabalin: A systematic review and meta‐analysis of randomized controlled trials

Abstract: SUMMARYPurpose: Despite the widespread use of antiepileptic drugs (AEDs) across different neurologic and psychiatric disorders, no study has systematically reviewed all available randomized controlled trials (RCTs) of a given AED to fully uncover its tolerability profile. We aimed at identifying treatment emergent adverse events (AEs) associated with pregabalin through a systematic review and meta-analysis of all available RCTs. We also assessed the association between serious AEs and pregabalin, and investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
133
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(148 citation statements)
references
References 56 publications
10
133
1
2
Order By: Relevance
“…Such adverse effects experienced in use of pregabalin are usually mild. 1,4 In contrast, the edema in our patient was severe enough to make us consider DVT. Wustmann 4 proposed a mechanism for the development of edema through K þ channels in smooth muscle cells.…”
Section: 2mentioning
confidence: 44%
See 1 more Smart Citation
“…Such adverse effects experienced in use of pregabalin are usually mild. 1,4 In contrast, the edema in our patient was severe enough to make us consider DVT. Wustmann 4 proposed a mechanism for the development of edema through K þ channels in smooth muscle cells.…”
Section: 2mentioning
confidence: 44%
“…[1][2][3][4][5] Although peripheral edema is one of the adverse effects, it was reported to be less common. 1,3,4 As deep venous thrombosis (DVT) is a life threatening complication, swelling in a limb is an important condition to be differentiated in spinal cord injury (SCI) patients. In search of the literature, we could reach only two case reports, regarding facial and feet edema in generalized anxiety disorder, and limb edema in posttraumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, about 40% of people had a diagnosis of dementia or some psychiatric disorder, and ≈50% were nonadherent to AED treatment within a year. In addition, Zaccara et al, in a meta‐analysis of placebo‐controlled trials, investigated differences in short‐term tolerability and adverse event profile across newer AEDs and found that pregabalin, the most frequently used AED in our cohort, was among the AEDs with a higher risk for intolerable adverse effects30, 31 …”
Section: Discussionmentioning
confidence: 84%
“…The starting dose is 50 mg BD which can be increased up to 600 mg/day. Common side effects of pregabalin are dizziness, vertigo, incoordination, balance disorder, ataxia, diplopia, blurred vision, amblyopia, tremor, somnolence, confusional state, and disturbance in attention, thinking abnormal, euphoria, asthenia, fatigue and peripheral edema [24].…”
Section: Criteria For Possible Etmentioning
confidence: 99%